2017
DOI: 10.18632/oncotarget.23174
|View full text |Cite
|
Sign up to set email alerts
|

Personalized therapy: CNS HGNET-BCOR responsiveness to arsenic trioxide combined with radiotherapy

Abstract: High-grade neuroepithelial tumor of the central nervous system with BCOR alteration (HGNET-BCOR) is a rare, highly malignant tumor. At the time of this publication, no standard protocol exists to treat this tumor entity. In this work, we tested the responsiveness of the primary culture PhKh1 derived from tumor tissue from a pediatric HGNET-BCOR patient (P1) to inhibitors of the Sonic hedgehog pathway combined with radiation. The SMO inhibitors vismodegib and itraconazole had low effect on the proliferation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 56 publications
2
30
1
Order By: Relevance
“…Martinez-Ricarte et al were able to classify 17 of 20 patients (including 2 children) with diffuse gliomas by analyzing only 7 genes in cell-free DNA from CSF [44]. Paret et al reported on one pediatric case of neuroepithelial high-grade tumor of the central nervous system showing a BCOR internal duplication, whose detection in plasma cell-free DNA correlated with relapse development [53]. The blood-brain barrier significantly restricts the amount of ctDNA entering the blood [7,22].…”
Section: Diagnostics and Therapeutic Stratificationmentioning
confidence: 99%
“…Martinez-Ricarte et al were able to classify 17 of 20 patients (including 2 children) with diffuse gliomas by analyzing only 7 genes in cell-free DNA from CSF [44]. Paret et al reported on one pediatric case of neuroepithelial high-grade tumor of the central nervous system showing a BCOR internal duplication, whose detection in plasma cell-free DNA correlated with relapse development [53]. The blood-brain barrier significantly restricts the amount of ctDNA entering the blood [7,22].…”
Section: Diagnostics and Therapeutic Stratificationmentioning
confidence: 99%
“…This combination led to a sustained complete remission for 7.5 years and the patient is alive more than 10 years after initial diagnosis. Remission and survival are much longer than of most previously reported cases (Table S1) 1‐2,5‐11 . However, since this is a novel entity, the follow up for most of these cases is short.…”
Section: Discussionmentioning
confidence: 72%
“…Currently, the ATO agent is used in the promyelocytic leukemia therapy 11 , but its clinical potential over other types of tumors continue to be underexplored. It has a well-recognized effect in suppressing the SHH pathway by inhibiting GLI proteins, a pathway related to human cancer pathogenesis 7,12,13 .…”
Section: Discussionmentioning
confidence: 99%